2012
DOI: 10.1183/09031936.00073911
|View full text |Cite
|
Sign up to set email alerts
|

Management of primary ciliary dyskinesia in European children: recommendations and clinical practice

Abstract: The European Respiratory Society Task Force on primary ciliary dyskinesia (PCD) in children recently published recommendations for diagnosis and management. This paper compares these recommendations with current clinical practice in Europe.Questionnaires were returned by 194 paediatric respiratory centres caring for PCD patients in 26 countries. In most countries, PCD care was not centralised, with a median (interquartile range) of 4 (2-9) patients treated per centre. Overall, 90% of centres had access to nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
32

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 20 publications
4
114
0
32
Order By: Relevance
“…The recent task force on PCD of the European Respiratory Society showed that 77% of centers have access to analyze by electron microscopy, 57% to ciliary function tests and only 36% of centers use the nasal nitric oxide test for PCD screening [30]. This task force found substantial heterogeneity in management of PCD within and between countries.…”
Section: Discussionmentioning
confidence: 99%
“…The recent task force on PCD of the European Respiratory Society showed that 77% of centers have access to analyze by electron microscopy, 57% to ciliary function tests and only 36% of centers use the nasal nitric oxide test for PCD screening [30]. This task force found substantial heterogeneity in management of PCD within and between countries.…”
Section: Discussionmentioning
confidence: 99%
“…A European survey reported wide variations between management strategies for PCD, highlighting differences between countries and within European regions [87]. The number of patients treated per centre was the most important predictor of choice of management strategy.…”
Section: Management Strategiesmentioning
confidence: 99%
“…Pasienter som har lav nNO-verdi eller pasienter der det finnes sterk klinisk mistanke om sykdommen, bør henvises til et spesialistsenter for å få diagnosen bekreftet (15). I Norge gjøres dette ved Oslo universitetssykehus, Rikshospitalet, som nylig er blitt godkjent som kompetansetjeneste for primaer ciliedyskinesi.…”
Section: Screening Og Diagnoseunclassified